Controlled biodegradation of polymers using nanoparticles and its application - Kumar S.; Maiti P. (My University, 2025)
The disposal of non-degradable plastics has increased exponentially as a result of poor recycling efficacy. The development of biodegradable plastics has become indispensable over the last two decades because of their origin from renewable resources. The potential interest in biodegradable plastics comes from the eco-friendly obliteration via microbial action which transforms the plastics into carbon dioxide and water resulting in a pollution-free natural system. Even though the lucrative interest lies in multiple areas, some of the properties such as brittleness, and poor thermal, mechanical and low gas barrier properties restrict their practical uses. The incorporation of nanoparticles in the polymer matrix or the fabrication of nanocomposites overcomes the shortcomings of the biodegradable polymers. To improve the aforementioned properties further, several approaches have been utilized, especially the incorporation of nanoparticles in the polymer matrix to prepare nanocomposites. One of the great advantages of nanoparticles is the ability to tune the rate of biodegradation (it is possible to both increase and decrease the rate as compared to that of the pure polymer) depending upon the need. Thus, chemical, physical and biological properties of the biodegradable polymers can be modified and controlled for sustainable applications in medicine and other areas. This review considers the major concerns of biodegradable polyesters and their nanocomposites, great details about the mechanism of their biodegradation, factors influencing their biodegradation and their applications in biomedical and packaging industries. © 2016 The Royal Society of Chemistry.